Remediation of Surface Water Polluted by Effluent Discharges from Mining Activities in the Eastern Region of Ghana - Kusi, S. (University of Ghana, 2017)
Heavy metals are very toxic to the environment and humans at large. Exposures to heavy metals have significant health disorders. In this research, the mandate to find novel adsorbent to reduce lead and mercury concentrations from water samples from Birim River in the Eastern Region of Ghana was studied. The turbidity of the water samples from Kibi, Anyinam and Kade indicated that, the river is very turbid (an average of 355 NTU) and therefore not recommended for domestic use without treatment. The modification of rice husk and orange peels with tartaric acid showed that modified rice husk had better binding efficiency for Pb and Hg. A series of batch experiments using tartaric acid modified rice husk (RH-TAM), tartaric acid orange peel modified (OP-TAM), unmodified rice husk (UM-RH) and unmodified orange peel (UM-OP) for the removal of Pb and Hg showed that the sorption processes depended on pH, contact time and adsorbent dosage. A pH of 5 with 0.5 g/20 ml of adsorbent solution maintained at a temperature of 35 o C ± 2 for a period of four (4) hours yielded the highest adsorption efficiency for both modified and unmodified adsorbents. The adsorption efficiencies recorded for RH –TAM and UM-RH were 75. 56 % and 69.93 % respectively for Pb. Similarly, Hg adsorption efficiencies for both RH-TAM and UM-RH were 53. 26 % and 45.11 % respectively. The adsorption efficiencies of OP –TAM was 62.03 % for Pb and 44.57% for Hg. The unmodified orange peel (UM-OP) had the least adsorption efficiencies of 51.88 % for Pb and 42.39% for Hg. The Langmuir isotherm fitted the experimental data for Pb and Hg better than the Freundlich isotherm.
Thesis (MPhil)
Keywords: Heavy metals; health disorders; Eastern Region of Ghana; Surface Water; Effluent Discharges; Mining